2023
DOI: 10.1093/jtm/taad081
|View full text |Cite
|
Sign up to set email alerts
|

Travel-related respiratory symptoms and infections in travellers (2000–22): a systematic review and meta-analysis

Abstract: Background: Respiratory tract infections (RTIs) are common in travellers due to the year-round or seasonal presence of respiratory pathogen and exposure to crowded environments during the itinerary. No study has systematically examined the burden of RTI infections among travellers. The aim of this systematic review and meta-analysis is to evaluate the prevalence of RTIs and symptoms suggestive of RTIs among travellers according to risk groups and/or geographic region, and to describe the spectrum of RTIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…In the cited study, SARS-CoV detected during the 2002--2003 outbreak accounted for 2% of all confirmed respiratory viral infections in travelers [9 ▪▪ ]. In this outbreak, more than 8000 individuals in 29 countries were affected, with a fatality rate of around 10%.…”
Section: Viral Infectionsmentioning
confidence: 95%
See 4 more Smart Citations
“…In the cited study, SARS-CoV detected during the 2002--2003 outbreak accounted for 2% of all confirmed respiratory viral infections in travelers [9 ▪▪ ]. In this outbreak, more than 8000 individuals in 29 countries were affected, with a fatality rate of around 10%.…”
Section: Viral Infectionsmentioning
confidence: 95%
“…The cause of respiratory infections in travelers appears to be similar to that of the local population [11]; in the previous review, in cases wherein a diagnosis was established based on molecular methods, the most common cause was viral (94%), followed by bacterial infections (6%), whereas fungal infections represented less than 1% [9 ▪▪ ].…”
Section: Epidemiology Of Respiratory Infections In Travelersmentioning
confidence: 97%
See 3 more Smart Citations